The Urgency of Packaging Houses in Accelerating Halal Certification For MSMEs Products in Jember Regency Indonesia - Mohammad Saleh; Umi Cholifah; Lusiana Ulfa Hardinawati; Suparman Suparman; Akhmad Munir (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study focused on the crucial role of packaging houses in expediting halal certification, particularly for Micro, Small Medium Enterprises (MSMEs) in Jember Regency. The objectives include analyzing the impact of packaging house quality on the halal certification of MSMEs products, exploring the role of packaging houses in accelerating the certification process, and assessing the repercussions of halal certification on product competitiveness in the local market. Using a mixed-method approach, the authors employed an exploratory sequential design. Focus Group Discussions emphasize the significant role of halal certification, challenges in MSMEs certification, and the vital role of packaging houses in the Jember Regency. Proposed solutions involve decentralization, training for Juru Sembelih Halal (Juleha) ‘Halal Slaughterers’, and collaborative efforts. Survey results indicate that MSMEs recognize the importance of packaging houses in expediting halal certification. However, facilities, systems, and regulations related to certification require more attention. Discussions confirm data validity and the ordinal logistic regression model, highlighting the crucial role of packaging houses in enhancing MSMEs awareness through training. Validation and reliability tests confirm research credibility, with t-tests revealing variations in MSMEs perceptions based on location, business type, and education. Research findings highlight the significant impact of packaging house quality on the halal certification process for MSMEs products in Jember Regency. High-quality packaging houses assist MSMEs practitioners in meeting halal certification requirements, enhancing consumer trust. The role of packaging houses in expediting the halal certification process is crucial, serving as guides. Halal certification significantly enhances consumer trust, expands the market, increases product competitiveness, and strengthens brand image.